Elementary School Student's Mathematical Literacy Skills: My Trip Math Adventure Game Learning Media - Sakinah, Sakinah; Mubarik, Mubarik; Pathuddin, Pathuddin; Alfisyahra, Alfisyahra (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study's objective is to determine the level of students' mathematical literacy skills before and after using the My Trip Math Adventure game. This research method uses a quantitative approach and employs a quasi-experimental design with a one-group pretest-posttest design. The sample of this study was grade V students of elementary school Inpres 15 Wara. The analysis technique used was descriptive statistical analysis and inferential statistical analysis. The results of the study indicated that there was an increase in students' mathematical literacy skills after the implementation of the My Trip Math Adventure game. The present study is based on the results of data analysis using descriptive statistics for students' mathematical literacy skills before the implementation of the My Trip Math Adventure game. Following the implementation of the My Trip Math Adventure game, 33% of students rated their mathematical literacy skills as high, while 67% rated them as very high. The results of the inferential statistical analysis (paired sample T-test) obtained a significance value of <0.05, which means that there was an increase in students' mathematical literacy skills after the implementation of the My Trip Math Adventure game in elementary school.